Ideas on language in early Latin Christianity from Tertullian to Isidore of Seville - Denecker, Tim. (Vigiliae Christianae, Supplements, 2017)
In Ideas on Language in Early Latin Christianity , Tim Denecker investigates, in a comprehensive and systematic way, the views held on the history, diversity and properties of language(s) by Christian Latin authors from Tertullian (b. c.160) to Isidore of Seville (d. 636). This historical period witnessed various sociocultural changes, affecting linguistic situations and the ways in which these were perceived. Christian intellectuals were confronted with languages other than Latin in the context of the propagation of faith, and in reflecting on language were bound to comply with the relevant biblical accounts. Whereas previous research has mostly focused on the (indeed vital) contribution of Augustine, the present study reveals the diversified and dynamic nature of linguistic reflection in early Latin Christianity.